Digital Investing: A Quantitative Analysis of Savings Preferences and Strategies Among Generation Z in Poland - Jakub KREZEL; Alicja KOZACKA; Wiktoria GALECKA (Communications of International Proceedings, 2025)
The digital transformation of the financial sector and new technologies have greatly expanded how people manage money and invest. Generation Z, raised with mobile apps and instant information access, is notably active in investing. They use traditional instruments like deposit accounts and bonds, alongside modern options such as cryptocurrencies, ETFs and micro-investments via apps. This study aimed to identify Generation Z’s investment preferences and the factors affecting their capital allocation. An online survey was conducted between February 24 and March 9, 2025, with 227 respondents aged 18-30 (52% women, 46% men). The findings reveal that Generation Z favors flexible, accessible investing methods, especially mobile apps and cryptocurrencies, but shows limited trust in traditional financial institutions. Risk attitudes vary widely, from conservative to speculative strategies. These insights inform recommendations for financial institutions to better tailor products and communication to young investors’ needs. The study emphasizes the critical role of financial education to support Generation Z in a fast-evolving market environment.
Keywords: digital investing; Generation Z; investment behavior; digital transformation